From Workplace to Third Place: How Japan’s Silver Human Resource Center Combines Work and Social Engagement After Retirement - Hanssen, M.; Fujita, N. (Journal of gerontological social work, 2025)
This study explores how Japanese retirees experience Silver Human Resource Centers (SHRCs). Based on in-depth interviews with 25 members, we investigated SHRCs' function as a workplace and a potential "third place." Our analysis revealed that members seek financial, health, and social benefits. We propose the concept of a "place 2.5," where SHRCs act as a hybrid space integrating work and social engagement. While identifying structural barriers, this study frames SHRCs as vital placemaking hubs that support fulfilling post-retirement lives and contribute to active aging research and program design.